PART INFORMATION SYSTEMS SERVICE CENTER PT. MICROSIS USING MICROSOFT ACCESS 2000 - Adi Setyawan; Drs. Sunarto Usna, MMSI (Jurnal Sistem Informasi, 2005)
With the implementation of information systems at the Service Center is expected to issues relating to availability of information can be solved.Given the complete data and supports the technician can more quickly and accurately analyze and repair the damaged goods.Computerized system error rate is smaller when compared with the manual system.Reports to the manager can be made quickly, accurately and more easily understood, so it helps managers in making decisions.